Exceptionally Long CDR3H Are Not Isotype Restricted in Bovine Immunoglobulins - Walther, Stefanie (Public Library of Science, 2013)
Exceptionally long third complementarity determining regions of the heavy chain (CDR3H) were previously described as a specificity of bovine IgG and IgM immunoglobulins. In addition, the genomic organization of the immunoglobulin heavy chain locus remains to be elucidated with a special focus on the number of variable segments (IGHV). By analyzing the variable regions according to the isotype-specific PCR using cDNA-PCR, we were able to prove the existence of exceptional long CDR3H in all bovine isotypes. The corresponding sequences of three distinct amplicons were grouped according to the length of the CDR3H. Sequences of CDR3H possessed 5 to 10, 12 to 31 or at least 48 amino acid residues. Long and mid-length CDR3H were composed of mainly hydrophilic amino acid residues, while short CDR3H also contained hydrophobic amino acid residues. All sequences with long CDR3H were related to the germline variable segment 10. Using the current genome assembly, Bos taurus NCBI build 6.1, the genomic organization of the bovine immunoglobulin heavy-chain locus was analyzed. A main locus was investigated on BTA21. Exons coding for variable, diversity, and joining segments, as well as for the constant regions of different isotypes, were also localized on BTA7, BTA8, and BTA20. Together with the information from unplaced contigs, 36 IGHV were detected of which 13 are putatively functional. Phylogenetic analysis revealed two bovine IGHV families (boVH1, boVH2). Thus, the existence of the two bovine families suggested was demonstrated, where boVH1 comprises all functional segments. This study substantially improves the understanding of the generation of immunoglobulin diversity in cattle.